FATORES ASSOCIADOS À OBESIDADE ABDOMINAL EM MULHERES PÓS-MENOPAUSA: UMA REVISÃO - Zanetti, Carolina; Franz, Ligia B. B.; Conte, Francieli; Turcatto, Marlon; Boff, Viviane S.; Busnello, Maristela B. (Salão do Conhecimento, 2013)
Resumo